The Implementation of Autonomous Learning in English Pronunciation of Guidance and Counseling Department’s Students - Maslakhatin, Maslakhatin; Lianawati, Ayong (JET ADI BUANA, 2017)
Most Indonesian students have difficulties in learning English pronunciation. Autonomous learning can be as an alternative strategy to help the students in learning pronunciation independently by utilizing Breakingnewsenglish.com. This study aimed to analyze the implementation of autonomous learning in learning pronunciation, the students’ response toward autonomous learning, and the impact of autonomous learning on the students’ pronunciation achievement. This study used descriptive qualitative method and the subject was Guidance and Counseling department students. The data was collected by observation, field notes, documentation, voice recording, and questionnaire. The result revealed that autonomous learning could be as an alternative strategy in learning pronunciation because the pronunciation performance of the students was significantly increased on the last meeting. They looked more enthusiastic in learning pronunciation autonomously.